1976
DOI: 10.1126/science.194.4270.1121
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Earth's Orbit: Pacemaker of the Ice Ages

Abstract: 1) Three indices of global climate have been monitored in the record of the past 450,000 years in Southern Hemisphere ocean-floor sediments. 2) Over the frequency range 10(-4) to 10(-5) cycle per year, climatic variance of these records is concentrated in three discrete spectral peaks at periods of 23,000, 42,000, and approximately 100,000 years. These peaks correspond to the dominant periods of the earth's solar orbit, and contain respectively about 10, 25, and 50 percent of the climatic variance. 3) The 42,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
1,623
2
48

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,393 publications
(1,724 citation statements)
references
References 55 publications
51
1,623
2
48
Order By: Relevance
“…During the Pleistocene, eccentricity maxima corresponded to warm periods (interglacials), while glacial periods occurred during eccentricity minima (Hays et al, 1976). In the early Pliocene, however, there was no eccentricity-related glacial-interglacial climatic regime.…”
Section: Astronomical Forcing and Tuning Of The Sedimentary Cycles Inmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Pleistocene, eccentricity maxima corresponded to warm periods (interglacials), while glacial periods occurred during eccentricity minima (Hays et al, 1976). In the early Pliocene, however, there was no eccentricity-related glacial-interglacial climatic regime.…”
Section: Astronomical Forcing and Tuning Of The Sedimentary Cycles Inmentioning
confidence: 99%
“…In summary, the cycles in Megalopolis look very similar to those in Lupoaia and they are dominated by the same astronomical period and moreover have the same phase relationship. Contrary to Lupoaia, which was deposited during a warm (early Pliocene) period, Megalopolis was deposited during the middle Pleistocene ice age regime, when 100 kyr (eccentricity) became the dominant astronomical (quasi-) period controlling glacial cyclicity (Hays et al, 1976;Imbrie et al, 1984).…”
Section: Lignite-dominated Lacustrine Basinsmentioning
confidence: 99%
“…One of the major challenges to the classical Milankovitch theory is the presence of 100 kyr cycles that dominate global ice volume and climate variability over the past million years (Hays et al, 1976;Imbrie et al, 1993;Paillard, 2001). This periodicity is practically absent in the principal "Milankovitch forcing" -variations of summer insolation…”
Section: Introductionmentioning
confidence: 99%
“…Introduction N.J. Shackleton's fundamental contributions to our understanding of climate variability at orbital timescales (10 4 -10 5 yr) continue to define the field today. Hays et al (1976) first established that the timing of variations in the Earth's orbit around the Sun corresponded to variations in Earth's climate over the last 430,000 years, providing strong support for the Milankovitch hypothesis for the cause of the ice ages. They also concluded that while climate responded linearly to precession (23 kyr) and obliquity (41 kyr), the dominant response over this interval has been to the small eccentricity forcing at 100 kyr, requiring some nonlinear amplification of the forcing.…”
mentioning
confidence: 99%